Do magnetic resonance imaging features differ between persons with multiple sclerosis of various races and ethnicities? - Nathoo, Nabeela; Zeydan, Burcu; Neyal, Nur; Chelf, Cynthia; Okuda, Darin T.; Kantarci, Orhun H. (Frontiers in Neurology, 2023)
Those of African American or Latin American descent have been demonstrated to have more severe clinical presentations of multiple sclerosis (MS) than non-Latin American White people with MS. Concurrently, radiological burden of disease on magnetic resonance imaging (MRI) in African Americans with MS has also been described as being more aggressive. Here, we review MRI studies in diverse racial and ethnic groups (adult and pediatric) investigating lesion burden, inflammation, neurodegeneration, and imaging response to disease modifying therapy. We also discuss why such disparities may exist beyond biology, and how future studies may provide greater insights into underlying differences, if any.